The Development of KlikMPK as an Affective Evaluation Platform for Indonesian Personality Development Course - Kadek Wirahyuni; I Nengah Suandi; I Nengah Martha; I Nyoman Sudiana (STAI Hubbulwathan Duri, 2022)
This research aimed to describe and analyze the results of developing an instrument, and an effective evaluation platform for Indonesian courses as a Personality and Development Courses at Universitas Pendidikan Ganesha called KlikMPK. This research was a type of research and development with the ADDIE model. This research involved two media experts. Research data were obtained from observations and questionnaires, then analyzed qualitatively and quantitatively. The results of this study indicated that 1) the advantages of the KlikMPK platform are that it is open-source, flexible and easy to use, secure and integrated; has plugin support and is easy to customize; as well as mobile-friendly and laptop support. 2) KlikMPK affective evaluation platform has a valid validity level with a score of 94.64. 3) The stages of development carried out include five stages in accordance with the ADDIE model. Thus, this platform can be used to evaluate the affective domain of students in Indonesian learning as Personality and Development Courses.